A Response to Commentaries - Cohen, I. Glenn (The Hastings Center report, 2016)
Our article “NFL Player Health Care: Addressing Club Doctors’ Conflicts of Interests and Promoting Player Trust” focused on an inherent structural conflict that faces club doctors in the National Football League. The conflict stems from club doctors’ dual role of providing medical care to players and providing strategic advice to clubs. We recommended assigning these roles to different individuals, with the medical staff members who are responsible for providing player care being chosen and subject to review and termination by a committee of medical experts selected equally by the NFL and the NFL Players Association. Recognizing that the problem of structural conflict of interest is deeply entrenched and that our recommendation is a significant departure from the status quo, we invited comment from a diverse and highly qualified group of experts. There is considerable common ground among the commentators. All but one agreed with us that, despite the best intentions of upstanding professionals, there is a structural conflict of interest in the club doctors’ relationship with players, and the commentaries were generally supportive of our recommendation for change. There are also meaningful disagreements, however. Some commentators think that the proposal is on the right track but does not go far enough to reduce the structural conflict of interest, and one commentary wholly disagrees with our analysis and recommendations.